2009
DOI: 10.1295/polymj.pj2009160
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Resin-Based Carbon Thin Fibers Prepared by Electrospinning: Additive Effects of Poly(vinyl butyral) and Electrolytes

Abstract: Phenolic resin-based carbon nanofibers with a diameter of about 110 nm, the highest electrical conductivity of 5.29 S/cm and highest BET specific surface area of 792.7 m 2 /g were prepared by electrospinning, followed by successive carbonization. The addition of a high-molecular-weight polymer, poly(vinyl butyral) (M w ¼ 340;000), and electrolytes, pyridine and sodium carbonate, to the phenolic resin/MeOH solution can effectively form a thinner smooth fiber by electrospinning, and then the as-spun fabrics were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 16 publications
1
57
0
Order By: Relevance
“…However, this drawback can be circumvented by designing an asymmetric supercapacitor using another type of active materials for the negative electrode of the supercapacitor [27], like carbon nanotubes or flexible electrospun carbon nanofibers [28]. Frequency range: 10 mHz to 500 kHz, signal amplitude 10 mV.…”
Section: Impedance Spectroscopymentioning
confidence: 99%
“…However, this drawback can be circumvented by designing an asymmetric supercapacitor using another type of active materials for the negative electrode of the supercapacitor [27], like carbon nanotubes or flexible electrospun carbon nanofibers [28]. Frequency range: 10 mHz to 500 kHz, signal amplitude 10 mV.…”
Section: Impedance Spectroscopymentioning
confidence: 99%
“…It is a high-molecular-weight polymer in the range of (170,000 -250,000) that helped improve the fibre formation as PVB showed good compatibility with phenolic resin (Suzuki et al 2007). Imaizumi et al (2009) reported that PVB could improve the electrospinnability by adjusting the solution viscosity (Table 2). Therefore electrospray deposition could be avoided and produced smooth fibre.…”
Section: Methodsmentioning
confidence: 99%
“…Novolac resin is produced with acidic catalyst at a ratio formaldehyde:phenol less than 1 while resole is obtained using alkaline catalyst at ratio beyond 1 (Raquez et al 2010). Both resins have their own uses in different fields such as adhesive for plywood , matrix for glass fibre composite (Amran et al 2015), resin for automotive moulding like suspension, seats and bottom plates (Plastics Today 2014) and electronic devices by producing electrospun fibre (Imaizumi et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Although any material with carbon back-bone can be used as precursor of carbon, carbon fibers are usually produced from three polymeric precursors: polyacrylonitrile (PAN), cellulose, and pitch [3,4]. Among these three precursors, PAN has received major attention due to its high carbon yield and superior mechanical properties of the resultant carbon fibers.…”
Section: Introductionmentioning
confidence: 99%